2001
DOI: 10.1093/geront/41.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Reminiscence, Personality, and Psychological Functioning in Older Adults

Abstract: The present study provides implications for both researchers and clinicians. Contrary to previous studies, results indicate that depressed and anxious older adults commonly use reminiscence and therefore may be appropriate candidates for reminiscence treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 31 publications
6
85
1
7
Order By: Relevance
“…That life review has greater effects on psychological well-being than plain reminiscence can also be explained on the basis of recent correlation/population studies. It was found that bitterness revival and boredom reduction correlate with higher levels of psychological distress and lower levels of life-satisfaction (Cappeliez et al, 2005;Cully et al, 2001). Integrative reminiscence (focusing on evaluation and synthesis) and instrumental reminiscence (focusing on former problem solving) were found to correlate with successful aging (Wong & Watt, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That life review has greater effects on psychological well-being than plain reminiscence can also be explained on the basis of recent correlation/population studies. It was found that bitterness revival and boredom reduction correlate with higher levels of psychological distress and lower levels of life-satisfaction (Cappeliez et al, 2005;Cully et al, 2001). Integrative reminiscence (focusing on evaluation and synthesis) and instrumental reminiscence (focusing on former problem solving) were found to correlate with successful aging (Wong & Watt, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Eight functions are discerned: boredom reduction, death preparation, identity-forming, conversation, intimacy maintenance, bitterness revival, teach/ inform, problem-solving. In a recent study using the RFS, it was found that higher levels of bitterness revival, boredom reduction, death preparation and total reminiscence correlated with higher levels of anxiety and that depression was correlated with bitterness revival (Cully et al, 2001). Cappeliez, O'Rourke and Chaudhury, (2005) found that boredom reduction and bitterness revival predicted lower life satisfaction, and death preparation predicted higher life satisfaction.…”
Section: Moderatorsmentioning
confidence: 99%
“…One type of psychotherapy that has been studied is participation in reminiscence therapy. This intervention is cost-effective and relatively free from harmful effect (7) . Reminiscence therapy can be defined as a therapy that uses the recall of past memories or stories, feelings and thoughts to facilitate pleasure, quality of life or adaptation to present circumstances (8).…”
Section: Introductionmentioning
confidence: 99%
“…Wink and Schiff (2002) suggest that only 30-50% of the older adults go through a process of life-review. In addition it has been found that some reminiscence styles (boredom reduction and bitterness revival) correlate strongly with both psychological distress and neurotic personality traits (Cully et al 2001;Cappeliez et al 2005). Theoretically this would make persons with these reminiscence styles prime candidates for life-review interventions, but it is yet unclear to what extent negative reminiscence styles can indeed be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Identity-forming reminiscence (similar to Integrative reminiscence or life-review) and problem-solving reminiscence (similar to instrumental reminiscence) have been found to correlate with successful aging (Wong and Watt 1991). Reminiscence for the sake of bitterness revival was found to correlate with higher levels of depression (Cully et al 2001;Cappeliez et al 2005). Therefore reminiscence as treatment of late-life depression should not only promote integrative reminiscence and problem-solving reminiscence but also reduce or transform bitterness-revival.…”
Section: Introductionmentioning
confidence: 98%